Generation of terahertz radiation by short laser pulses propagating in obliquely magnetized plasma. (20th April 2021) - Mishra, Dinkar; Sharma, Pooja; Singh, Saumya; Kumar, Bhupesh; Jha, Pallavi
Abstract: This paper presents an analytical and simulation study of terahertz (THz) radiation generation using short, circularly polarized laser pulses propagating in plasma embedded in arbitrarily oriented magnetic field. Perturbation technique is used to obtain generated electric and magnetic wakefields within and behind the laser pulse. Coupling of components of the obliquely applied magnetic field with transverse and axial plasma electron velocities leads to the generation of linearly as well as elliptically polarized transverse electromagnetic radiation oscillating at THz frequency, under appropriate conditions. The amplitude of these fields and ellipticity of the elliptically polarized THz radiation can be varied with the help of the obliqueness of the external magnetic field. Analytical results are validated using VSim PIC simulation code.